Diversification at financial institutions and systemic crises - Wagner, Wolf (Journal of Financial Intermediation, 2010)
It is widely believed that diversification at financial institutions benefits the stability of the financial system. This paper shows that it also entails a cost: even though diversification reduces each institution’s individual probability of failure, it makes systemic crises more likely. When systemic crises induce additional costs (over and above individual failures), full diversification is no longer desirable as a result and the optimal degree of diversification may be arbitrarily low. We show that the analysis can be extended beyond diversification, such as to interbank insurance and financial integration.